Measurement dielectric constant of transformer oil at frequency 18 to 26 GHz (K-Band) / Nurul Elieya Che Muda - Che Muda, Nurul Elieya (2008)
The complex reflection coefficient (real and imaginary) are measured using Vector Network Analyzer (VNA). In this project, present a method for measurement of dielectric properties of transformer oil using metal-back method. Complex reflection coefficient (Sn) is measured for Plexiglas container backed by metal plate. Dielectric constants and loss factors were measured for new and used transformer oil in the frequency range of 18 to 26 GHz (K-Band). The thru, reflect and line (TRL) calibration technique were used to eliminate the effect of undesirable multiple reflection. The measurement system consist of Vector Network Analyzer (VNA), a pair of spot focusing horn lens antenna, mode transitions, coaxial cable and computer .A computer program was developed for calculation of complex reflection coefficient. Data fro VNA measurement is the input to this program.